Saccade Dynamics in the Acute and Recovery Phase of Abducens Nerve Palsy - Elissavet Kemanetzoglou; Klio Chatzistefanou; Nikolaos Smyrnis; Evangelia Kararizou; Evangelos Anagnostou (Journal of Ophthalmic & Vision Research)
Purpose: To examine the natural adaptive course of ocular motor system in unilateral abducens nerve palsy while addressing the scarce literature on saccade dynamics and natural adaptation. Methods: Binocular horizontal eye movements were recorded from 18 healthy adults and 21 adults with unilateral abducens nerve palsy during the acute and chronic phases. Dynamics of the paretic and non-paretic eyes were compared, and the non-paretic eye dynamics were correlated with the respective prism diopters. Non-parametric tests were used for statistical comparisons. Results: The paretic eye, compared to the non-paretic eye, presented a slightly lower saccadic gain and velocity/amplitude ratio and a higher duration/amplitude ratio. The nonparetic eye, compared to healthy controls, showed consistent amplitude gain (>1) and a tendency for a higher duration/amplitude ratio. In the acute phase, when the non-paretic eye was covered, the paretic eye’s amplitude ratio was lower and the duration/amplitude ratio decreased significantly. In the acute phase, a greater degree of esotropia in the paretic eye was associated with a lower amplitude gain and duration/amplitude ratio in the nonparetic eye. Conclusion: During adaptation in abducens nerve palsy, the saccade duration of the paretic eye increased, and a similar tendency was observed in the non-paretic eye. This finding likely reflects a change in the “pulse-step” pattern and may be related to plastic changes in central structures, such as the cerebellum, that support learning processes.